E Protein Transcription Factors as Suppressors of T Lymphocyte Acute Lymphoblastic Leukemia - Parriott, Geoffrey; Kee, Barbara L. (Frontiers in Immunology, 2022)
T Lymphocyte Acute Lymphoblastic Leukemia (ALL) is an aggressive disease arising from transformation of T lymphocytes during their development. The mutation spectrum of T-ALL has revealed critical regulators of the growth and differentiation of normal and leukemic T lymphocytes. Approximately, 60% of T-ALLs show aberrant expression of the hematopoietic stem cell-associated helix-loop-helix transcription factors TAL1 and LYL1. TAL1 and LYL1 function in multiprotein complexes that regulate gene expression in T-ALL but they also antagonize the function of the E protein homodimers that are critical regulators of T cell development. Mice lacking E2A, or ectopically expressing TAL1, LYL1, or other inhibitors of E protein function in T cell progenitors, also succumb to an aggressive T-ALL-like disease highlighting that E proteins promote T cell development and suppress leukemogenesis. In this review, we discuss the role of E2A in T cell development and how alterations in E protein function underlie leukemogenesis. We focus on the role of TAL1 and LYL1 and the genes that are dysregulated in E2a-/- T cell progenitors that contribute to human T-ALL. These studies reveal novel mechanisms of transformation and provide insights into potential therapeutic targets for intervention in this disease.